Time-varying Meshing Stiffness Calculation of Spur Gears with Asymmetric Spalling Defects - Han, Wenqiang; Jiang, Hanjun (International Journal of Mechanical and Electrical Engineering, 2024)
Gear systems are subjected to repeated loads during long-term operation, and factors such as insufficient lubricant to increase friction between gears, resulting in elevated temperatures and wear, are highly susceptible to tooth spalling. Tooth spalling is a common form of failure in gear failure. In previous studies, the vibration response of a gear pair with spalling defects at the tooth center near the pitch circle has been investigated. However, the location of the spalling defects offset from the center of the tooth flank is rarely studied. Tooth spalling faults occur in the pitch circle, but not necessarily in the center of the tooth, often formed on both sides of the center of the tooth and torsion in the meshing process. the symmetric and asymmetric rectangular spalling defects are considered, the torsional deformation is introduced. “torsional stiffness” is introduced into the overall TVMS due to the spalling defect. Therefore, it is meaningful to grasp the reasons for the formation of tooth spalling.